THE EFFECT OF AIRGAP THICKNESS ON THERMAL PROTECTIVE PERFORMANCE IN HEAT RESISTANT CLOTHING - Fuad, Ainul; Yao, Jiafeng; Wahyudi, Slamet; Siswanto, Eko (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2024)
The thermal protective performance is provided by thermal protective clothing worn by people who work in high temperature environments and is highly influenced by air gaps. In this paper, effect of air gap thickness on thermal protective performance as indicated by the time before degree burn were investigated. 3 layers of thermal protective clothing with 3 types of fabrics that have been selected will be tested using an experimental method. The research will be conducted through experimental tests using the fabric level method on a bench-scale test apparatus which is equipped with 4 thermocouples and using gas torch as a heat source. The air gap located between the layers of thermal protective clothing will be varied with different thickness in a vertical orientation. The size of the air gap used varies from 01 mm, 2.51 mm, 51 mm, and 7.51 mm. The results show that the temperature distribution in each layer of clothing from the outer shell to the thermal linear has decreased. In addition, time before degree burn which is an indicator on thermal protective performance shows a positive effect on the addition of air gap thickness where the optimum air gap thickness is shown at 7.5 mm variation. It is hoped that the results of this research can be a source or useful information in mechanical engineering, especially in the fields of thermal comfort and fire safety.